Tungsten Removal From Chemical Mechanical Polishing (CMP) Spent Slurry Using Dowex Monosphere MR-450 Ultrapure Water (UPW) Resin - Shamshuddin Jaya, Haslina (Universiti Sains Malaysia, 2018)
In the modern semiconductor manufacturing processes, chemical mechanical polishing (CMP) has grown to be an essential part of the production of integrated circuit (IC) manufacturing. It involves the polishing of metallic surface by chemical action followed by the removal of the modified layer by mechanical action using tungsten slurry. Ion exchange process is used extremely for the removal of ionized impurities with proper resin selection. Therefore, ion exchange is one of the options to remove the heavy metal from spent slurry and to achieve environmental benefits that arise from the removal. The aim of this research is to study the removal mechanisms of tungsten, W, as a typical microelectronic metal under different resin loadings. Furthermore, surface analysis techniques which are scanning electron microscope (SEM) analysis and energy dispersive X-Ray (EDX) analysis were performed to study the characterization of the mixed bed resin with the CMP spent slurry. Concentration of tungsten removal was evaluated using inductively coupled plasma mass spectrometer (ICP-MS) by varying the amount of Dowex monosphere MR-450 UPW mixed resin loadings (5g, 10g, 15g and 20g) at constant pH slurry under batch process. It is found that this mixed resin is effective to remove tungsten for more than 96% from spent tungsten CMP slurry at pH 3.87 ± 0.02. However, the removal percentage decreases from 98% to 96% as the resin loadings amount increases due to an increase in the availability of more sorption sites. Optimum resin loading was found to be 5g for 100 mL of spent slurry as it give the highest removal of tungsten which is 98%.